Design and test of a collecting machine for orchard waste fruit pouches - Hu, Caiqi; Teng, Fengjie; Hu, Xiaoqi; Smirnov, Igor; Du, Kun; Liu, Dongyu; Liang, Qiaojun (International Journal of Agricultural and Biological Engineering, 2025)
In response to the issues posed by non-biodegradable orchard fruit pouches causing environmental pollution, as well as the inefficiency and high cost of manual recovery, a design for an orchard fruit pouch collecting machine was proposed. The study involved analyzing the structure and working principle of the entire machine, as well as proposing two types of pick-up and recovery devices: a spring-tooth roller type pickup device and an air-suction collecting device. After comparative analysis, the spring-tooth roller type pickup device was selected. Based on the physical characteristics of the fruit pouch, theoretical calculations and kinematic analysis were performed for the key components of the orchard fruit pouch collecting machine. This analysis yielded working parameters for each component, with a focus on roller rotational speed, machine travel speed, and number of spring-tooth rows as critical factors influencing operational effectiveness. Subsequently, the ADAMS simulations were conducted based on these findings. Then the response surface methodology was applied, and an optimal parameter combination for the orchard fruit pouch collecting machine was determined: a machine travel speed of 2 km/h, roller rotational speed of 60 r/min, and five rows of spring teeth. The prototype was made, and the results of orchard experiments indicated that with the optimal parameter combination, the recovery rate predicted by the model was 85.2% and that of the orchard experiment was 80.9%. The relative error between them is 5.3%. These findings confirmed that the designed orchard fruit pouch collecting machine could achieve the expected performance and effectively recover fruit pouches with good efficiency. Key words: waste fruit pouches; collecting machinery; structure design; ADAMS simulation analysis; orchard experiment DOI: 10.25165/j.ijabe.20251806.9411 Citation: Hu C Q, Teng F J, Hu X Q, Smirnov I, Du K, Liu D Y, et al. Design and test of a collecting machine for orchard waste fruit pouches. Int J Agric & Biol Eng, 2025; 18(6): 104–111.